SEISMIC CHARACTERISTICS OF VARIABLE CONVECTION AT ERTA 'ALE LAVA LAKE, ETHIOPIA - Jones J.; Malone S.; Carniel R.; Harris A.J.L. (My University, 2006)
The active summit lava lake of Erta 'Ale volcano, Ethiopia, offers a unique opportunity to study magma convection. In February 2002, we collected a multiparametric set of seismic, thermal and video data. These data indicate that the lake cycled between periods characterized by low (0.01-0.08 m s- 1) and high (0.1-0.4 m s- 1) convection rates, typically lasting tens to hundreds of minutes. Three seismometers placed around the active crater recorded continuous tremor with a dominant frequency of 2 Hz, and energy at frequencies from 0.8 to 12 Hz. Here, we characterize the seismic signature of each regime by its spectral content, wavefield polarization, and tremor source location. For both regimes, the wavefield is mostly rectilinear. Azimuths and incidence angles are consistent with P waves originating in one of two locations: the north edge of the active lava lake, or a region 100-150 m ENE of the lava lake. Because both regimes are dominated by a low frequency, rectilinearly polarized wavefield, we investigate the source location using a method that solves for location and isotropic source power by a weighted least-squares amplitude-based inversion of seismic data. We find that tremor source regions are unique to each convective regime, although some location overlap exists when tremor is located in short time windows. Wavefield composition suggests that the convective phases may share a common source process, but their differing locations indicate that either the source region is non-stationary, or a second source skews the location during the high convective phase. Tremor polarization and location suggests that the low-frequency tremor is caused by bubble coalescence and bursting in a conduit whose surface is the lava lake. The higher frequency signal associated with the high convective regime is associated with a scattered, more complex wavefield superimposed on the low-frequency background tremor, caused by bubble bursting and cracking of cooled crust at the lava lake surface. © 2005 Elsevier B.V. All rights reserved.
Keywords: CONVECTION; ERTA ALE; LAVA LAKES; POLARIZATION ANALYSIS; SEISMIC; SEISMIC SOURCE LOCATION; THERMAL; VOLCANIC TREMOR